Review of the drill and blast parameters to reduce dilution at Scort-Scoop CA Mine, Ivory Coast - Maiga, Souleymane (University of Mines and Technology, 2021)
The underground mining of narrow veins is mostly associated with dilution. Dilution is the contamination of ore by non-ore material, which consequently increases tonnage and reduces grade. Excessive dilution is an often-cited challenge that has a direct and significant influence on the cost, and ultimately on the profitability of a mining project. SCORT-COOP CA (SSC) is a small-scale mining company located in Moronou, Ivory Coast, which employs square-set method in its mining process. Drilling and blasting practices at SSC were reviewed from March 2020 to December 2020. Using statistical data analysis, the old blast design recorded average dilution of 34% whereas the modified blast design reduced the average dilution to 24.68%. The new blast design contributes to the economic stability of the mine with a net profit of CFA 100 million. However, SSC mine will not be a viable project when the dilution level exceeds 46%. Stope performance review should be conducted periodically to improve on the blast design. Also, planning and technical service team can organize dilution awareness campaigns to inform personnel about the implications of ore dilution levels on viability of SSC project.
x, 75p. ill.
Keywords: Blasting; Extractive industry; Mining processes; Drilling